The Challenges in Using "BELA BARIS’ Application in ELT for Young Learners - Anggraeni, Dian Puspita; Fitriati, Sri Wuli (Language Circle: Journal of Language and Literature, 2025)
Young learners exhibit distinct characteristics that distinguish them from adult learners. Therefore, teachers need innovative methods to accommodate the unique characteristics of young learners when teaching them English. The BELA BARIS application serves as one of the innovations in English Language Teaching (ELT) for young learners. However, there are some challenges that teachers face in implementing the application. This study aims to explain the difficulties encountered when using the BELA BARIS application in ELT with young learners. This study employs a single instrumental case study within a descriptive qualitative research design. The participants in this study are an English teacher and fifth-grade students at SDIT Sahabat in Karanganyar Regency. The data were obtained from observations and interviews of both students and teacher. This study found that there are four challenges associated with using digital applications for teaching English to young learners: 1) poor internet connection, 2) insufficient digital literacy skills among students, 3) significant time required for preparation, and 4) limited availability of devices. The use of the BELA BARIS application presents an opportunity for effective English learning for young learners, but it also poses challenges that teachers face. The researcher suggests that primary school teachers incorporate it into their teaching methods.